Enzimas antioxidantes en cerebro de cobayos nativos de las grandes alturas - Pajuelo T., Mónica (2004)
We have determined antiaxidant enzyme activities of: Superoxide Dismutase (SOD), Glutatione Peroxidase (GPx) and Catalase (CAT); levels of malondialdehyde (MDA) and hydroperoxids as lipoperoxidation indicators, and phospholilpase activity as mediator of the lipoperoxidation in cerebral tissue of guinea pigs born and bred in Cerro de Pasco at 4 300 m (ALT), with respect to guinea pigs at sea level (NM), in order to detect real differences between both groups. With respect to activity of antioxidant enzymes, we have not found significant differences between both groups. In the study group (ALT) we have found significant differences in the activity of phospholipase and level of hydroperoxides (p < 0.01 Y P < 0.001. respectively) as compared to sea level group. Also, we have found that level of MDA is significantly less in the study group (p < 0.01).Thus, observed data would lead us to say that altitude does not influence activity of antioxidant enzymes in cerebral tissue of guinea pigs, but it probably influences level of lipoperoxidation, due to a major activity of phospholipase and level of hydroperoxides; nevertheless, a minor level of MDA would indicate the participation of other antioxidant mechanisms.